Revitalisasi Motif Batik Reog Ponorogo dalam Karya Tari Batik Ponoragan - Annursyah, Hasbi; Aminudin, Aminudin; Wibowo, Anggono Kusumo (Gesture: Jurnal Seni Tari, 2025)
This study investigates the revitalization of Reog Ponorogo batik motifs through the creation of a contemporary dance performance entitled Tari Batik Ponoragan. The research aims to reinterpret the symbolic meanings and philosophical values embedded in Reog Ponorogo batik motifs into choreographic language and visual presentation. A qualitative approach was employed, incorporating participant-led and practice-led methods that actively engaged local batik artisans and dancers in the creative process. Data were obtained through participatory observation, in-depth interviews, and documentation, and analyzed thematically. The results demonstrate that this revitalization effort successfully integrates cultural symbolism with expressive and innovative choreography, resulting in an authentic work of art. Beyond artistic espression this dance also serves an educational medium and a means of reinforcing cultural identity sustainability. Collaborative, inclusive, and practice-bassed approaches are proven to be effective strategies for preserving and developing cultural heritage in respons to contemporary social changes.